Evaluasi Kejadian Pembatalan Operasi Elektif di Instalasi Bedah Sentral RSUP Dr Kariadi Semarang - Anto Indriyadi; Chriswardani Suryawati (Jurnal Manajemen Kesehatan Indonesia, 2020)
Cancellation of elective surgery causes harm to the hospital and patients so it needs to be prevented by using a risk management approach. The purpose of this research is to evaluate the control system for canceling elective operations in hospitals after studying the FMEA method (Failure Mode Effects Analysis).This was qualitative research design presented in explanatory design. The main informants in this study included elements of management and practitioners in the hospital. Triangulation informants included patients and head of the room. Data were collected by in-depth interview and observation techniques. The researcher analyzes using content analysisThe results of the study showed that cancellation of elective surgery was mostly due to the health condition of the patient. Cancellation of human resource factors is caused by doctors who experience fatigue. Cancellation because the operating room is caused because the operating schedule is not appropriate. Cancellation due to device factors due to unavailability of implants.This study recommends increasing the range of preoperative studies, and increasing coordination for equalizing the workload of operators. While suggestions for hospitals are in the form of adding operator  adding operating devices and repairing SIRS for markers of operations.